Cyberbullying Against Female : The Case of Indonesian Celebrities - Fikri (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Cyberbullying has been noted as one of the fundamental problems in the world that needs thoughtful action. It is treated this way due to the range and the risk it may create. There have been abundant studies on cyberbullying that focus on the cases undergone by celebrities. However, there still needs some further research concerned on how cyberbullying cases take place in Indonesian contexts linguistically. This study aims to provide insight on the cyberbullying cases experienced by Indonesian female celebrities based on linguistic point of view. The data were collected from the comments left by Instagram users on Indonesian female celebrities’ Instagram accounts. The data were subsequently classified into cyberbullying forms. Speech acts classifications theory by Searle (1969) and Yule (1996) are used in this study to identify the intention of the comment left by the netizens as well as to analyse the findings. It is shown through the result of this study that cyberbullying toward Indonesian female celebrities attacks physical appearance dominantly through the form of flaming and harassment cyberbullying. Speech acts found from the netizen’s utterances are representatives, expressives, and directives using indirect form of language uses. This implies that in term of gender-based cyberbullying, Indonesia netizens commonly attack the sexuality, behaviour, and physical appearance including face, clothing, and body shape.